John Van Woerth correspondence - Van Woerth, John.
ALS written by Van Woerth at Saratoga Springs, N.Y., to Phinehas Gage at Fort Miller, N.Y., regarding shipment of provisions for the Continental Army during the Revolution.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gage, Phinehas -- Correspondence; United States. -- Continental Army -- Supplies and stores; Fort Miller (N.Y.) -- History; New York (State) -- History -- Revolution, 1775-1783.; Saratoga Springs (N.Y.) -- History; United States -- History -- Revolution, 1775-1783.; Army officers